Rln3a is a prerequisite for spermatogenesis and fertility in male fish. Issue 197 (March 2020) - Yang, Lanying; Li, Yanlong; Wu, You; Sun, Shaohua; Song, Qiang; Wei, Jing; Sun, Lina; Li, Minghui; Wang, Deshou; Zhou, Linyan
Highlights: Mutation of rln3a gene severely affected the spermatogenesis, sperm maturation and fertility in XY male fish. The deficiency of Rln3a suppressed the expressions of steroidogenic enzyme genes, subsequently declined 11-KT synthesis. hCG failed to rescue the decrease of 11-KT, while hRLN3 considerably improved the sperm motility in rln3a −/− XY fish. Abstract: The essential roles of Relaxin3 (RLN3) in energy homeostasis had been well investigated, while the mechanisms of RLN3 regulating reproduction remain to be elusive in mammals. Although two rln3 paralogues have been characterized in several teleosts, their functions still remain largely unknown. In this study, two paralogous rln3 genes, represented as rln3a and rln3b, were identified from the testis of Nile tilapia ( Oreochromis niloticus ). Rln3a was dominantly expressed in testis, while the most abundant rln3b expression was in brain. In situ hybridization demonstrated that rln3a is abundantly expressed in the Leydig cells of the testis. To understand the role of Rln3 in the testicular development, homologous null- rln3a gene mutant line was constructed by CRISPR/Cas9 technology. Morphological observation demonstrated that null mutation of rln3a gene caused testicular hypertrophy and a significant increase of GSI. However, a significant decrease of spermatogenic cells at different phases, i.e. spermatogonia, spermatocytes, spermatids and sperms was found. Silencing of rln3a gene repressed the expression of key genes in germ cell and Leydig cell. Deficiency of Rln3a led to the significant decrease of 11-KT production, which stimulated the up-regulation of both FSH and LH production in the pituitary via a negative feedback manner possibly. Mutation of rln3a in XY fish led to the hypogonadism with sperm deformation, significant decrease of fertility, and sperm motility, revealing as the high mortality of the offspring obtained by crossing the wild type female and rln3a −/− XY fish. Interestingly, recombinant human RLN3 injection significantly enhanced the sperm motility in rln3a −/− XY fish. Moreover, hCG treatment stimulated the expression of steroidogenic enzyme genes and 11-KT production, which were repressed by rln3a mutation in XY fish. Taken together, this study, for the first time by using a gene knockout model, proved that Rln3a is an indispensable mediator for androgen production in testis via HPG axis, and plays an essential role in spermatogenesis, sperm motility and male fertility in fish.